Early history of operative treatment of fractures - Bartoníček, Jan (Archives of orthopaedic and trauma surgery, 2010)
Surgery in the first half of the nineteenth century was primarily dominated by pain and fear of lethal infections. Therefore, the absolute majority of fractures and dislocations were treated non-operatively. Development of operative treatment of fractures was influenced by three major inventions: anaesthesia (1846), antisepsis (1865) and X-rays (1895). The first to use external fixation is traditionally considered to be Malgaigne (1843). However, his devices cannot be considered as external fixation. Von der Höhe, in 1843, fixed a non-union of the femur by inserting into both fragments a couple of screws transversely connected outside the wound. Von Langenbeck in 1855 treated a non-union of the humerus with screws connected by a devise designed for this purpose. A predecessor of nailing of acute diaphyseal fractures may be considered to be fixation of diaphyseal non-unions of the femur, humerus and tibia with ivory intramedullary pegs, performed by Dieffenbach in 1846. Nevertheless, until 1885, osteosynthesis was still a Cinderella having at its disposal mainly wires, ivory pegs and very primitive types of external fixation. During the following 35 years (1886-1921), operative treatment of fractures witnessed an unprecedented revolution. Radiology became an integral part of bone and joint surgery. All types of osteosynthesis, i.e. plates (Hansmann 1886), external fixation (Parkhill 1897) and intramedullary nails (Schöne 1913) were introduced into clinical practice. Basic experiments were undertaken, surgical approaches described and the first textbooks on osteosynthesis published.
Keywords: fixace fraktury; dějiny 19. století; Humans; Fractures, Bone; fraktury kostí; History, 20th Century; dějiny 20. století; lidé; History, 19th Century; Fracture Fixation